Sex and Ethnic Differences in Career Decision Self-Efficacy: The Comparison between Mentawai, Kutai, Lombok, Palu, and Papua Youths - Situmorang, Dominikus David Biondi; Lewoleba, Magdalena Palang (Bulletin of Counseling and Psychotherapy, 2025)
Career Decision Self-Efficacy (CDSE), which reflects an individual's confidence in making effective career decisions, is influenced by various factors, particularly sex and ethnicity. This quantitative, non-experimental cross-sectional study aims to compare CDSE levels among young men and women from five ethnic groups in Indonesia: Mentawai, Kutai, Lombok, Palu, and Papua. The study involved 75 participants, 38 males and 37 females—who completed the Career Decision Self-Efficacy Scale–Short Form (CDSES-SF), which demonstrated high reliability (Cronbach’s alpha = 0.901). The results revealed gender-based differences in CDSE dimensions. Male participants scored highest in goal selection (M = 4.79, SD = 0.66) and lowest in planning for the future (M = 4.48, SD = 0.67). In contrast, female participants showed the highest score in occupational information (M = 4.74, SD = 0.61) and the lowest in problem solving (M = 4.43, SD = 0.82). Ethnic differences were also observed. The lowest scoring CDSE dimensions varied: occupational information for Mentawai (M = 4.32, SD = 0.61) and Palu (M = 4.24, SD = 0.43); planning for the future for Kutai (M = 3.70, SD = 0.81) and Papua (M = 3.37, SD = 0.56); and goal selection for Lombok (M = 3.57, SD = 0.88). Based on these findings, it is recommended that counselors provide group or classical guidance and career-focused counseling/psychotherapy to help students strengthen CDSE dimensions where scores remain low, thereby supporting informed and confident career decision-making.